Fibroepithelial polyp with sebaceous hyperplasia: A case report - P K Rajeesh Mohammed; Basanta Kumar Choudhury; Radha Prasanna Dalai; Vivek Rana (Indian Journal of Medical and Paediatric Oncology)
Fibro epithelial Polyp (FEP) is a polypoid outgrowth of epidermis and dermal fibro vascular tissue. This polyp is most commonly found in oral cavity, neck and axilla, though any skin fold may be affected like groin area. We describe a case of a 25-year-old male patient with a growth over the anterior rugae region of hard palate since 3 years. Based on histological appearance, diagnosis of sebaceous gland hyperplasia in fibroepithelial polyp was given which itself is a rare entity, and in our case, it was encountered at the rarest of sites.